A rare, likely pathogenic GCK variant related to maturity-onset diabetes of the young type 2: A case report - So, Min-Kyung; Huh, Jungwon; Kim, Hae Soon (Journal of genetic medicine, 2021)
Maturity-onset diabetes of the young (MODY) is caused by autosomal dominant pathogenic variants in one of 14 currently known monogenic genes. Characteristics of patients with MODY include early-onset clinical disease with a family history of diabetes and negative autoantibodies and may present with heterogeneous phenotypes according to the different subtypes. Here, we report a patient with early-onset diabetes who presented asymptomatic mild fasting hyperglycemia with the absence of autoantibodies. She was diagnosed with glucokinase (GCK)-MODY caused by a GCK variant, c.1289T>C (p.L430P), identified by targeted gene-panel testing, and the affected father had the same variant. We interpreted this rare missense variant as a likely pathogenic variant and then she stopped taking oral medication. This case highlights the usefulness of genepanel testing for accurate diagnosis and appropriate management of MODY. We also note the importance of familial genetic testing and genetic counseling for the proper interpretation of MODY variants. KCI Citation Count: 0